Protective effects of metformin on cardiovascular system - Vujovic, Slavica; Scepanovic, Andjelka (Progress in Nutrition, 2020)
For several decades now, metformin has been a first medicine of choice in the treatment of diabetes mellitus type 2 primarily characterized by insulin resistance. Except as a monotherapy or in cases metformin is not sufficient on its own, it is combined with other anti – diabetic medication. Metformin is recommended as diabetes therapy, because, unlike other medications, it does not threaten the occurrence of hypoglycemia since it does not stimulate the secretion of insulin in pancreaticβ- cells but it disposes of free insulin that has already been secreted. Besides its anti – diabetic effects, metformin demonstrates the pleiotropy of effects on various diseases and issues related to metabolism. For the last ten years, metformin has been greatly tested as a treatment of polycystic ovary syndrome, prediabetes, cardiovascular diseases, but also as a produce to destroy cancer cells and potential produce to prolong the life expectancy. It creates the antihyperglycemic effect by inhibiting gluconeogenesis in the liver and increasing the sensitivity of the tissue by stimulating its receptors for insulin. Besides, this medication increases the intensity of glycolysis, inhibits the effects of glucagon and stimulates the fatty acid oxidation. Certainly, the result of this effect is the reduction of the level of glucose in the blood and a reduction of fatty acid accumulation. However, despite the benefits that metformin hasin treating diabetes type II in the first place, and then other metabolic issues both related to insulin resistance and those beyond this framework, a chronic usage of metformin has proven in some research to have insufficient effectand to lead to the body becoming saturated therewith.Thorough survey into the effects of this medication shall be continued, in order to determine its place not only as an accessible and certain medicine for insulin resistance, but also as applicable in both prevention and treatment of a numerous other metabolic issues.